Preparation method of single crystal type solid electrolyte

By using a single crystal solid electrolyte method in the preparation process of solid electrolyte, the problem of volume expansion and sticking to crucible walls in the solid phase method is solved, and efficient lithium ion conduction and battery performance are achieved.

CN119725698APending Publication Date: 2025-03-28SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909515.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing solid-phase method has severe clotted wall phenomenon and volume expansion problems when preparing LATP solid electrolytes, resulting in low production efficiency and the prepared powder has a large grain boundary, hindering the conduction of lithium ions.

Method used

A single crystal solid electrolyte is prepared by using a method of preparing a single crystal solid electrolyte, including calcining the ion source mixture to obtain a polycrystalline electrolyte, and then mixing it with a lithium supplement agent and heat treatment to form a single crystal electrolyte.

Benefits of technology

By reducing the grain boundaries, the ionic conductivity of the solid electrolyte is improved, and the problems of volume expansion and sticking to the crucible wall in traditional methods are solved, and the performance and efficiency of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725698A_ABST
    Figure CN119725698A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a single crystal type solid electrolyte, which comprises the following steps: S1, calcining an ion source mixture to obtain a polycrystalline solid electrolyte; s2, mixing the polycrystalline solid electrolyte with a lithium supplement agent to obtain a lithium supplement mixture; and S3, carrying out heat treatment on the lithium supplementing mixture to form the single crystal type solid electrolyte. Therefore, the formed single crystal type solid electrolyte is relatively low in half-peak width value and has better conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to the field of battery materials, and specifically, to a solid electrolyte. Background Art

[0002] Due to the many advantages of lithium-ion batteries, such as high energy density and long life, lithium ions are an indispensable energy storage unit in current electronic devices. Lithium-ion batteries that use liquid electrolytes have safety hazards such as leakage and combustion. In contrast, lithium batteries that use solid electrolytes have better battery performance, including operating voltage and energy density, because solid electrolytes composed of solid ion conductors can form a structurally stable lithium ion transmission channel at the microscopic level and the electrochemical stability window of solid electrolytes is wide. At the same time, because there is no above-mentioned disadvantages of liquid electrolyte leakage, etc., it has higher safety and stability, and has become a current research hotspot.

[0003] At present, solid electrolytes mainly include: organic system, oxide system and sulfide system. Among them, the solid electrolytes of oxide system mainly include lithium lanthanum titanium oxide (LLTO) with perovskite structure, lithium lanthanum zirconium oxide (LLZO) with garnet structure, fast ion conductors (LISICON, NASICON), etc. The advantages of solid electrolytes of these oxide systems come from the inherent properties of inorganic oxides: high mechanical strength, high physicochemical stability, strong pressure resistance, and low manufacturing complexity. Furthermore, the advantages of NASICON-type oxide electrolytes are more prominent. Taking lithium aluminum titanium phosphate (LATP) as an example, they include: high ionic conductivity, wide electrochemical stability window, mechanical stability and mechanical strength that are conducive to processing, good chemical stability in air, and low cost due to the absence of expensive elements.

[0004] Common methods for preparing LATP include solid-phase method, melt quenching method, mechanical activation method, sol-gel method, co-precipitation method and hydrothermal method; among them, the solid-phase method has the lowest cost and the strongest operability, but the solid-phase sintering will cause serious sticking to the crucible wall, making it difficult to separate the material from the crucible; in addition, there is a serious volume expansion problem, that is, the volume from raw material to finished product will increase by more than 5 times, which greatly reduces the production efficiency of the solid-phase method.

[0005] After many tests and analyses, it was found that the reasons for these problems are: the phosphorus sources produced by the LATP or LAGP solid phase method are mainly ammonium phosphate, ammonium monohydrogen phosphate or diammonium hydrogen phosphate. These substances will decompose into liquid phosphoric acid when heated to above 300°C. As the temperature continues to rise, the LATP synthesis reaction occurs, and lithium carbonate decomposes to produce a large amount of carbon dioxide gas, causing the volume to expand several times; at the same time, the appearance of liquid products also leads to enhanced contact between the raw material and the crucible wall, making it firmly adhere to the crucible.

[0006] Moreover, the LATP powder prepared in this way often has more grain boundaries, which will pose a considerable obstacle to the conduction of lithium ions in the future. Summary of the invention

[0007] In order to solve the aforementioned problems, including achieving the effect of reducing or even eliminating grain boundaries in the solid electrolyte, the present invention particularly discloses a method for preparing a single-crystal solid electrolyte, which comprises the following steps: S1: calcining an ion source mixture to obtain a polycrystalline solid electrolyte; S2: mixing the polycrystalline solid electrolyte with a lithium replenisher to obtain a lithium replenishing mixture; and S3: heat-treating the lithium replenishing mixture to form the single-crystal solid electrolyte.

[0008] In some embodiments, the ion source includes a lithium source (Li).

[0009] In some embodiments, the ion source further includes an aluminum source (Al), a titanium source (Ti), a phosphorus source (P), a zirconium source (Zr), or any combination thereof.

[0010] In some embodiments, the ion source is a combination of a lithium source (Li), an aluminum source (Al), a titanium source (Ti), and a phosphorus source (P), and the stoichiometric ratio thereof is Li (1+x) Al (x) Ti (2-x) P3, wherein x is from 0.2 to 0.6.

[0011] In some embodiments, the lithium source (Li) includes lithium nitrate, lithium carbonate, lithium dihydrogen phosphate, lithium chloride, lithium sulfide, lithium fluoride or lithium acetate, the aluminum source (Al) includes aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum nitrate or aluminum acetate, the titanium source (Ti) includes titanium dioxide, tetrabutyl titanate or titanium isopropoxide, the phosphorus source (P) includes phosphorus pentoxide, phosphoric acid, ammonium phosphate, ammonium monohydrogen phosphate or diamine hydrogen phosphate, and the zirconium source (Zr) includes zirconium dioxide, zirconium carbonate, zirconium silicate or zirconium oxychloride.

[0012] In some embodiments, the ion source mixture further includes an adsorbent.

[0013] In some embodiments, the adsorbent includes graphite, activated carbon, coke, graphene, carbon nanotubes, or any combination thereof.

[0014] In some embodiments, the adsorbent accounts for 0.1 to 30% by weight of the ion source mixture.

[0015] In some embodiments, the lithium supplement comprises lithium carbonate, lithium acetate, or any combination thereof.

[0016] In some embodiments, the molar amount of lithium in the lithium supplementer accounts for 0.5 to 30% of the molar amount of lithium in the single crystal solid electrolyte.

[0017] In some embodiments, the heat treatment is performed at a temperature of 400 to 1200° C., and the heat treatment time is 2 to 30 hours.

[0018] In some embodiments, S1 includes: S11: keeping the ion source mixture at a first temperature for a first time, and then keeping it at a second temperature for a second time to obtain a first calcined mixture; and S12: keeping the first calcined mixture at a third temperature for a third time to obtain the polycrystalline solid electrolyte; wherein the first temperature is less than the second temperature, and the second temperature is equal to the third temperature.

[0019] In some embodiments, the first temperature is 300 to 400°C, the second temperature is 600 to 1200°C, and the third temperature is 600 to 1200°C.

[0020] In some embodiments, the preparation method further comprises a screening step.

[0021] In some embodiments, the screening step further includes a first screening step and a second screening step, wherein the first screening step is between S11 and S12, and is for processing the first calcined mixture; the second screening step is between S12 and S2, and is for processing the polycrystalline solid electrolyte.

[0022] The present invention further provides a single crystal solid electrolyte, which is prepared by the method for preparing the single crystal solid electrolyte as described above.

[0023] The present invention further provides a battery having the above-mentioned single crystal solid electrolyte.

[0024] Accordingly, the effects provided by the present invention include but are not limited to: (1) the single-crystal solid electrolyte produced has a lower half-width and a larger particle size. In other words, the number of grain boundaries will be reduced, which can achieve improved conductivity and solve traditional problems; (2) Due to the effect of the adsorbent, the loss in the production process of the single-crystal solid electrolyte is less; (3) It can also be understood that the solid electrolyte provided by the present invention can be used in batteries and can improve the quality and performance of the batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the first flow chart of the method for preparing a single-crystal solid electrolyte.

[0026] Figure 2 This is the second flow chart of the method for preparing a single-crystal solid electrolyte. DETAILED DESCRIPTION

[0027] The essential features of the present invention are further illustrated by combining the following embodiments.

[0028] The present invention provides a method for preparing a solid electrolyte. By using an ion supplement and high temperature treatment, the grain boundaries of the solid electrolyte can be reduced, thereby improving the performance of the solid electrolyte. Specifically, by providing the method for preparing a solid electrolyte, the ionic conductivity of the prepared solid electrolyte can exceed 10 -4 S / cm, compared with the solid electrolyte prepared by the general preparation method, its ionic conductivity is 10 -5 S / cm, increased by 10 times.

[0029] In terms of results, the solid electrolyte preparation method can be said to be a solid electrolyte "converted" from polycrystalline to single crystal. In terms of grain boundaries, polycrystalline has more grain boundaries than single crystal, and single crystal is larger than polycrystalline in terms of primary particle size. The solid electrolyte is not limited, but includes organic solid electrolyte, oxidized solid electrolyte or sulfide solid electrolyte; the oxidized solid electrolyte includes LLTO, LLZO, LATP and LiPON. Specifically, the molecular formula of LLTO can be Li 0.33 La 0.56 TiO3, which belongs to the perovskite type; the molecular formula of LLZO can be Li7La3Zr2O 12 , which belongs to the garnet type; the molecular formula of LATP can be Li 1.3 Al 0.3 Ti 1.7 (PO4)3, which belongs to NASICON type (sodium super ion conductor type); LiPON can be nitrogen-doped Li3PO4, which belongs to LISICON type (lithium super ion conductor type). The method provided by the present invention does not exclude that it can be used for the conversion of the above-mentioned solid electrolyte.

[0030] As for the ion supplement, it is used as a lithium supplement in some embodiments, but it can also be understood that the ion supplement will be different corresponding to different solid electrolytes. Therefore, in some embodiments, the ion supplement further includes a lithium (Li) supplement, an aluminum (Al) supplement, a titanium (Ti) supplement, a zirconium (Zr) supplement, a lanthanum (La) supplement, or any combination thereof, without limitation.

[0031] Please refer to Figure 1The present invention particularly discloses a method S for preparing a single-crystal solid electrolyte, which comprises the following steps: a calcination step S1: calcining an ion source mixture to obtain a polycrystalline solid electrolyte; a lithium replenisher mixing step S2: mixing the polycrystalline solid electrolyte with a lithium replenisher to obtain a lithium replenisher mixture; and a heat treatment step S3: heat treating the lithium replenisher mixture to form the single-crystal solid electrolyte.

[0032] In some embodiments, the ion source mixture is a mixture of an ion source and an adsorbent.

[0033] In some embodiments, the ion source includes a lithium source (Li).

[0034] In some embodiments, the ion source further includes an aluminum source (Al), a titanium source (Ti), a phosphorus source (P) or any combination thereof; it is understandable that the combination of the ion sources can produce a solid electrolyte including LLTO, LLZO, LATP or LiPON after a calcination step.

[0035] In some embodiments, the ion source is a combination of a lithium source (Li), an aluminum source (Al), a titanium source (Ti), and a phosphorus source (P), wherein the stoichiometric ratio is Li (1+x) Al (x) Ti (2-x) P3, wherein x is 0.2 to 0.6; for example, the stoichiometric ratio of the lithium source (Li) is (1+x) x (1.0 to 1.3), and taking x=0.3 as an example, the stoichiometric ratio of Li should be fed at 1.3 to 1.69. It can be understood that such an ion source combination can produce the LATP.

[0036] In some embodiments, the lithium source (Li) includes lithium nitrate, lithium carbonate, lithium dihydrogen phosphate, lithium chloride, lithium sulfide, lithium fluoride or lithium acetate, the aluminum source (Al) includes aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum nitrate or aluminum acetate, the titanium source (Ti) includes titanium dioxide, tetrabutyl titanate or titanium isopropoxide, the phosphorus source (P) includes phosphorus pentoxide, phosphoric acid, ammonium phosphate, ammonium monohydrogen phosphate or diamine hydrogen phosphate, and the zirconium source (Zr) includes zirconium dioxide, zirconium carbonate, zirconium silicate or zirconium oxychloride.

[0037] In some embodiments, the adsorbent includes graphite, activated carbon, coke, graphene, carbon nanotubes, or any combination thereof.

[0038] It can be understood that the adsorbent here is a liquid phase adsorbent. For example, when carbon is calcined in a temperature range of 300°C to 400°C, the liquid phosphoric acid produced in this temperature range can be kept separated from other ion sources (powders) to a certain extent; thereby, the permeability of the ion source mixture can be enhanced, so that the gas generated by the decomposition of any ion source in the ion source mixture during the calcination step can be discharged in time, reducing the volume expansion multiple of the ion source mixture in the subsequent calcination step. At the same time, the products of the calcination step, including the first calcined mixture and the polycrystalline solid electrolyte, are separated from their container, such as the crucible wall, so that the above products can be smoothly taken out after the calcination step, that is, after sintering is completed.

[0039] In some embodiments, the mass ratio of the adsorbent to the ion source is 1:(2.3 to 1000). In some embodiments, the adsorbent accounts for 0.1 to 30% of the ion source mixture, preferably 2% to 20%, and more preferably 5% to 10%.

[0040] In some embodiments, the lithium supplement includes lithium carbonate (Li2CO3), lithium acetate (CH3COOLi) or any combination thereof; herein, the lithium supplement includes other lithium salts, and any lithium salts that can provide lithium ions are not excluded.

[0041] In some embodiments, the molar amount of lithium in the lithium supplement agent accounts for 0.5 to 30% of the molar amount of lithium in the single crystal solid electrolyte, preferably 1 to 25%, and more preferably 1 to 20%.

[0042] In some embodiments, the heat treatment is between 400 and 1200°C, preferably between 500 and 1000°C.

[0043] In some embodiments, the heat treatment time is 2 to 30 hours, preferably 4 to 24 hours, and more preferably 8 to 20 hours.

[0044] In some embodiments, please refer to Figure 2 The calcination step S1 includes: a first calcination step S11: keeping the ion source mixture at a first temperature for a first time, and then keeping it at a second temperature for a second time to obtain a first calcined mixture; and a second calcination step S12: keeping the first calcined mixture at a third temperature for a third time to obtain the polycrystalline solid electrolyte.

[0045] In some embodiments, the first temperature is less than the second temperature, and the second temperature is equal to the third temperature.

[0046] In some embodiments, the first temperature is 300 to 400°C, preferably 320 to 380°C; the second temperature is 600 to 1200°C, preferably 750 to 1050°C; the third temperature is 600 to 1200°C, preferably 750 to 1050°C.

[0047] In some embodiments, the first time is less than the second time, and the second time is greater than the third time.

[0048] In some embodiments, the first time is 0.1 to 10 hours, preferably 0.1 to 5 hours, more preferably 0.5 to 2 hours; the second time is 0.1 to 30 hours, preferably 0.1 to 10 hours, more preferably 0.5 to 4 hours; the third time is 0.1 to 30 hours, preferably 0.1 to 10 hours, more preferably 0.5 to 4 hours.

[0049] In some embodiments, please refer to Figure 1 and Figure 2 The preparation method S further includes a screening step, and the screening step further includes a first screening step S111 and a second screening step S121, wherein the first screening step S111 is between the first calcination step S11 and the second calcination step S12, and is for processing the first calcined mixture, and the second screening step S121 is between the second calcination step S12 and the lithium supplement mixing step S2, and is for processing the polycrystalline solid electrolyte.

[0050] In some embodiments, the first screening step S111 is to pass the first calcined mixture through a 5 to 2000 mesh sieve, and the second screening step S121 is to pass the polycrystalline solid electrolyte through a 5 to 2000 mesh sieve.

[0051] In some embodiments, in the first screening step S111, the mesh number through which the first calcined mixture passes is smaller than the mesh number through which the polycrystalline solid electrolyte passes in the second screening step S121.

[0052] The present invention further provides a single crystal solid electrolyte, which is prepared by the preparation method S of the single crystal solid electrolyte as described above.

[0053] The present invention further provides a battery having the above-mentioned single crystal solid electrolyte.

[0054] Below, specific embodiments and comparative examples are provided to facilitate understanding of the technical features of the present invention.

[0055] Here you can refer to Figure 2The single crystal solid electrolyte provided in the following specific embodiments or comparative examples is formed by including: a first mixing step S10, a first calcination step S11, a first screening step S111, a second calcination step S12, a second screening step S121, a lithium supplement mixing step S2 and a heat treatment step S3, which are described as follows.

[0056] Example 1

[0057] First mixing step S10: According to the stoichiometric ratio: Li 1.43 Al 0.3 Ti 1.7 (PO4)3, lithium dihydrogen phosphate, aluminum oxide, titanium dioxide, diammonium hydrogen phosphate and activated carbon are uniformly mixed to obtain an ion source mixture, wherein the amount of activated carbon added accounts for 8wt% of the ion source mixture;

[0058] First calcination step S11: the ion source mixture is first kept at 360° C. for 1 hour, then calcined at 900° C. for 2 hours, and then cooled to room temperature to obtain a first calcined mixture;

[0059] First screening step S111: crushing / pulverizing the first calcined mixture and passing it through a 100-mesh sieve to obtain a first calcined crushed product;

[0060] The second calcination step S12: the first calcined crushed product is kept at 900° C. for 1 hour, and then cooled to room temperature to obtain a polycrystalline solid electrolyte;

[0061] Second screening step S121: crushing / grinding the polycrystalline solid electrolyte and passing it through a 200-mesh sieve to obtain a polycrystalline solid electrolyte powder;

[0062] Lithium supplement mixing step S2 and heat treatment step S3: The polycrystalline solid electrolyte powder and lithium carbonate are mixed evenly, and the mixture is kept at 500° C. for 12 hours to form a single crystal solid electrolyte (LATP); wherein the molar amount of lithium in the lithium carbonate accounts for 1% of the molar amount of lithium in the single crystal solid electrolyte.

[0063] The difference between Example 2 and Example 1 is that in the lithium supplement mixing step S2 and the heat treatment step S3, the polycrystalline solid electrolyte powder and lithium carbonate are evenly mixed and kept at 900° C. for 20 hours to form a single crystal solid electrolyte (LATP); wherein the molar amount of lithium in the lithium carbonate accounts for 4% of the molar amount of lithium in the single crystal solid electrolyte.

[0064] The difference between Example 3 and Example 1 is that in the lithium supplement mixing step S2 and the heat treatment step S3, the polycrystalline solid electrolyte powder and lithium acetate are evenly mixed and kept at 900° C. for 16 hours to form a single crystal solid electrolyte (LATP); wherein the molar amount of lithium in the lithium acetate accounts for 8% of the molar amount of lithium in the single crystal solid electrolyte.

[0065] The difference between Example 4 and Example 1 is that in the lithium supplement mixing step S2 and the heat treatment step S3: the polycrystalline solid electrolyte powder and lithium carbonate are mixed evenly, and the mixture is kept at 1000° C. for 16 hours to form a single crystal solid electrolyte (LATP); wherein the molar amount of lithium in the lithium carbonate accounts for 20% of the molar amount of lithium in the single crystal solid electrolyte.

[0066] The difference between Example 5 and Example 1 is that in the lithium supplement mixing step S2 and the heat treatment step S3: the polycrystalline solid electrolyte powder and lithium carbonate are mixed evenly, and the mixture is kept at 700° C. for 15 hours to form a single crystal solid electrolyte (LATP); wherein the molar amount of lithium in the lithium carbonate accounts for 2% of the molar amount of lithium in the single crystal solid electrolyte.

[0067] The difference between Example 6 and Example 1 is that in the lithium supplement mixing step S2 and the heat treatment step S3, the polycrystalline solid electrolyte powder and lithium acetate are evenly mixed and kept at 1000° C. for 9 hours to form a single crystal solid electrolyte (LATP); wherein the molar amount of lithium in the lithium acetate accounts for 16% of the molar amount of lithium in the single crystal solid electrolyte.

[0068] The difference between Comparative Example 1 and Example 1 is that the lithium supplement mixing step S2 and the heat treatment step S3 are not included, and a polycrystalline solid electrolyte (LATP) is formed.

[0069] The difference between Comparative Example 2 and Example 1 is that in the first mixing step S10, 0.08 wt% of activated carbon is added.

[0070] The difference between Comparative Example 3 and Example 1 is that in the first mixing step S10, 32 wt% of activated carbon is added.

[0071] For the grain size analysis of the final products produced by the above-mentioned embodiments or comparative examples, i.e., the single crystal solid electrolyte (LATP) and the polycrystalline solid electrolyte (LATP), an X-ray diffractometer is used to test the XRD spectrum of the powder sample. The test conditions are 10-70°, a step length of 0.02°, a scanning speed of 10° / min, and the half-height width (Full Widthat Half Maximum, FWHM, radians) of the strongest peak at (113) is used as the reference, and the Scherrer formula is used to estimate the size D of the primary particle size.

[0072] The above Scherrer formula is expressed as: D = Kλ / (βcosθ), where D is the grain size (nm), K is the Scherrer constant (usually 0.9), λ is the X-ray wavelength (nm), β is the full width at half maximum (FWHM, radians) of the peak, and θ is the Bragg angle (radians).

[0073] The technical differences between the embodiments and the comparative examples are shown in Table 1.

[0074] Table 1

[0075] The differences in efficacy between Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 2.

[0076] Table 2

[0077] It can be found from Table 2 that the half-peak widths of Examples 1 to 6 are smaller and the primary particle sizes are larger than those of Comparative Examples 1 to 3. Such results mean that the number of grain boundaries is relatively reduced through the lithium supplementation agent mixing step S2 and the heat treatment step S3, and the polycrystalline solid electrolyte can be turned into a single-crystalline solid electrolyte, which can be expected to bring about better conductivity effects.

[0078] Further observing Example 5 and Example 6, the proportion of activated carbon is 1wt% and 16wt% respectively. Compared with Examples 1 to 4, the half-peak width of the material has no obvious change, and the proportion of activated carbon only affects its processing efficiency and cost.

[0079] In Comparative Examples 1 to 3, there is no significant change in the half-peak width of the material, and the proportion of activated carbon only affects its processing efficiency and cost.

[0080] The above are only several preferred embodiments of the present invention, but they cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification should fall within the patent protection scope of the present invention.

Claims

1. A method for preparing a single crystal solid electrolyte, comprising the following steps: S1: calcining the ion source mixture to obtain a polycrystalline solid electrolyte; S2: mixing the polycrystalline solid electrolyte with a lithium replenishing agent to obtain a lithium replenishing mixture; and S3: heat-treating the lithium-supplementing mixture to form the single-crystal solid electrolyte.

2. The preparation method according to claim 1, wherein The ion source includes a lithium source (Li).

3. The preparation method according to claim 1, wherein The ion source further includes an aluminum source (Al), a titanium source (Ti), a phosphorus source (P), a zirconium source (Zr) or any combination thereof.

4. The preparation method according to claim 2, wherein The ion source is a combination of a lithium source (Li), an aluminum source (Al), a titanium source (Ti) and a phosphorus source (P), and the stoichiometric ratio is Li (1+x) Al (x) Ti (2-x) P3, wherein x is from 0.2 to 0.

6.

5. The preparation method according to claim 2, wherein: The lithium source (Li) includes lithium nitrate, lithium carbonate, lithium dihydrogen phosphate, lithium chloride, lithium sulfide, lithium fluoride or lithium acetate, the aluminum source (Al) includes aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum nitrate or aluminum acetate, the titanium source (Ti) includes titanium dioxide, tetrabutyl titanate or titanium isopropoxide, the phosphorus source (P) includes phosphorus pentoxide, phosphoric acid, ammonium phosphate, ammonium monohydrogen phosphate or diamine hydrogen phosphate, and the zirconium source (Zr) includes zirconium dioxide, zirconium carbonate, zirconium silicate or zirconium oxychloride.

6. The preparation method according to claim 1, wherein The ion source mixture also includes an adsorbent.

7. The preparation method according to claim 6, wherein The adsorbent includes graphite, activated carbon, coke, graphene, carbon nanotubes or any combination thereof.

8. The preparation method according to claim 6, wherein The adsorbent accounts for 0.1 to 30% of the ion source mixture.

9. The preparation method according to claim 1, wherein The lithium supplement includes lithium carbonate, lithium acetate or any combination thereof.

10. The preparation method according to claim 9, wherein The molar amount of lithium in the lithium supplement agent accounts for 0.5 to 30% of the molar amount of lithium in the single crystal solid electrolyte.

11. The preparation method according to claim 1, wherein The heat treatment temperature is 400 to 1200° C., and the heat treatment time is 2 to 30 hours.

12. The preparation method according to claim 1, wherein The S1 includes: S11: keeping the ion source mixture at a first temperature for a first time, and then keeping it at a second temperature for a second time, to obtain a first calcined mixture; and S12: keeping the first calcined mixture at a third temperature for a third time to obtain the polycrystalline solid electrolyte; The first temperature is lower than the second temperature, and the second temperature is equal to the third temperature.

13. The preparation method according to claim 10, wherein: The first temperature is 300 to 400°C, the second temperature is 600 to 1200°C, and the third temperature is 600 to 1200°C. The preparation method according to claim 10 , further comprising a screening step.

15. The preparation method as described in claim 10, wherein the screening step also includes a first screening step and a second screening step, wherein the first screening step is between the S11 and the S12, and is for processing the first calcined mixture, and the second screening step is between the S12 and the S2, and is for processing the polycrystalline solid electrolyte.

16. A single crystal solid electrolyte, prepared by the preparation method according to any one of claims 1 to 15.

17. A battery comprising the single crystal solid electrolyte according to claim 16.